2014
DOI: 10.1016/j.jfoodeng.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of variogram analysis to classify field peas with and without internal defects caused by weevil infestation

Abstract: In this study, we acquired 72 (training data) and 30 (independent validation) high-spatial resolution (7 by 7 pixels per mm 2 ) hyperspectral imaging data [240 spectral bands from 392 to 889 nm (spectral resolution = 2.1 nm)] from samples of field peas (Pisum sativum) with and without pea weevil (Bruchus pisorum) infestation. The reflectance data were analyzed with linear discriminant analysis (LDA) or either reflectance values only or of a combination of reflectance values and variogram parameters (derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Spectral binning was deployed, as it has been shown to increase classification accuracy [23,40]. Similar previously published studies [24,40], a radiometric filter was applied to exclude background, so that a pixel was only included, if the reflectance value of Acacia and Banksia seed coat at 660 nm (R660) met the following criterion: 0:050 < R660 < 0:250…”
Section: Hyperspectral Imaging Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral binning was deployed, as it has been shown to increase classification accuracy [23,40]. Similar previously published studies [24,40], a radiometric filter was applied to exclude background, so that a pixel was only included, if the reflectance value of Acacia and Banksia seed coat at 660 nm (R660) met the following criterion: 0:050 < R660 < 0:250…”
Section: Hyperspectral Imaging Data Analysismentioning
confidence: 99%
“…Several studies have demonstrated the potential of reflectancebased spectroscopy methods in studies of plant seeds, including detection of internal infestations by weevils (Bruchus pisorum) in dry field peas (Pisum sativum) [23,24], classification of near isogenic maize lines (Zea mays) [25], ageing of cabbage seeds [26], classification of near isogenic maize lines (Z. mays) [27], differentiation between black walnut (Juglans nigra) shell and pulp [28], sorting of lettuce (Lactuca sativa) seeds [29], and viability of horticultural seeds [26,30,31]. These spectroscopy studies are based on the fundamental assumption that reflectance data acquired from the seed coat provides indicative information about the quality/ germination of the given seed.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with classical taxonomy (under the microscope) or molecular-based classification of minute and closely related animals, plant seeds and growing plants, a reflectance-based method may be of considerable relevance to a wide range of biological studies. There are numerous approaches to classification of hyperspectral imaging data, and only recently has the approach (a combination of variogram analysis and linear discriminant analysis) used in this study been described and successfully applied (Nansen, 2012;Nansen et al, 2010a;Nansen et al, 2009;Nansen et al, 2014). However, this analysis represents the first application of this classification method to the identification of animals.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of reflectance data was based on a combination of variogram analysis (Nansen, 2012;Nansen et al, 2014) and linear discriminant analysis (Fisher, 1936). In brief, the analytical approach consists of conducting variogram analysis of reflectance values in individual spectral bands from each hyperspectral image.…”
Section: Reflectance Data Processing and Analysismentioning
confidence: 99%
“…The approach has been used to detect damage and internal infestation in food products, including field peas (Pisum sativum) (100,158), wheat kernels (Triticum aestivum) (125,126), soy beans (Glycine max) (52), and jujubes (Ziziphus jujuba) (139,140). In addition, thermal imaging (reflectance in the 8-12 ”m range) has been used to detect infestations by a stored grain beetle (Cryptolestes ferrugineus) inside wheat kernels (80) and infestations by insects in a wide range of other food products (136).…”
Section: Cryptic Insect Infestationsmentioning
confidence: 99%